(untitled) (Journal of Hama University, 2020)
The aim of this research is to identify the nature of the relationship between Hypocrite personality and self-control among a sample of students of Damascus University, according to the variable (male, female). The Hypocrite personality scale was used to prepare (Dulaimi, 2004) and the researcher adjustment, self-control (Badr, 2017) and the researcher adjustment, and the number of respondents as a whole (350) students. The study reached the following results: • A high level of Hypocrite personality among the members of the research sample. • There is a positive correlation of statistically significant between the Hypocrite personality and Self-control among the members of the research sample. • There are no statistically significant differences between the mean scores of the research sample on the Hypocrite personality scale according to sex variable (male, female). 4. There are no statistically significant differences between the mean scores of the research sample on the Self-control scale according to gender variable (male, female).